Notes on the natural history and identity of the pelagic sea snake Hydrophis platurus (Serpentes: Elapidae) from Golfo Dulce, Puntarenas, Costa Rica - Solórzano-Lopez, Alejandro (2024)
Introduction: The pelagic sea snake Hydrophis platurus has the broadest distributional range of all the snakes and is the only sea snake of tropical waters off the west coast of the Americas. Within the variation in the color pattern of this species, completely yellow specimens were considered very rare or occasional. However, a yellow pattern dominates a population established in the interior of the Golfo Dulce in the Southern Pacific of Costa Rica. Objective: We studied the abundance, activity patterns, morphometry, and feeding behavior of the yellow H. platurus within the Golfo Dulce. Methods: Between February 2009 and July 2018, we conducted surveys for sea snakes from a boat within the perimeter of the Golfo Dulce. Results: Adults from the gulf population are smaller than the bicolor oceanic population, with females having larger bodies. Sea snakes within the gulf float and move with surface currents without being linked to drift lines and debris. These snakes are mainly found in clean, calm waters with little turbulence. They feed on a wide diversity of small fish, which they capture using passive stalking predatory behaviors floating on the surface. Prey are quickly captured and swallowed alive. This species has an almost total absence of predation, a pattern that extends to this yellow population. Conclusions: The characteristics of the gulf and the direction and strength of the surface currents at its entrance might restrict the transit of this yellow population to the outside and the entry of the bicolored snakes of the oceanic population. We do not consider making taxonomic changes in this Golfo Dulce population prudent. This yellow population is relatively common within the basin. However, the high tourist traffic and other activities are risk factors for its conservation. Protection policies must be created to preserve and protect this small population of yellow sea snakes unique within this species' distribution range.